1999
DOI: 10.1016/s0038-1098(99)00196-9
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy magnetic excitations in the dimerized and incommensurate phase of CuGeO3

Abstract: Low-energy magnetic excitations in the dimerized (D) and incommensurate (I) phase of CuGeO 3 were studied by Raman spectroscopy. Based on temperature and magnetic field dependent experiments on pure and Si-doped samples the Raman peak at 17 cm Ϫ1 for T 2 K in the D-phase is attributed to a soliton-assisted one-magnon excitation. We further present a Ramanstudy of the low-energy spin dynamics of a spin-Peierls system in the incommensurate phase. The magnetic field induced transition between D-and I-phase of CuG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…3. The same gap energy (2.3±0.2 cm −1 ≈ 0.29 meV) was observed in a Raman experiment [18], which mainly probes the structural excitations, pointing to a magneto-structural origin for this excitation. We attribute the mode at 0.29 meV to phase oscillations of the soliton lattice, so-called phasons.…”
Section: + δKsp)supporting
confidence: 76%
“…3. The same gap energy (2.3±0.2 cm −1 ≈ 0.29 meV) was observed in a Raman experiment [18], which mainly probes the structural excitations, pointing to a magneto-structural origin for this excitation. We attribute the mode at 0.29 meV to phase oscillations of the soliton lattice, so-called phasons.…”
Section: + δKsp)supporting
confidence: 76%
“…15,16,17 One-magnon modes of comparable energies have also been observed in Raman scattering experiments on the two-dimensional antiferromagnet La 2 CuO 4 .…”
mentioning
confidence: 62%
“…30 He and his coworkers also studied Raman scattering of pure CuGeO 3 under high magnetic fields and reported that the spin-gap mode was activated in the IC phase, while it is Raman inactive in the SP phase. 29,30,33 Moreover, the two-magnetic-excitation bound state gradually disappeared as the magnetic field was increased in the IC phase.…”
Section: Magnetic-field Effectsmentioning
confidence: 99%
“…29,30,33 Moreover, the two-magnetic-excitation bound state gradually disappeared as the magnetic field was increased in the IC phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation